Employee privileges in the Polish tobacco industry in a period of Polish People’s Republic - Synowiec, Andrzej (Studia Historiae Oeconomicae, 2015)
Described privileges of determined employee groups in the Polish tobacco industry in a period of Polish People’s Republic on example of Kraków plants arose largely from the statute law, although not without meaning carried out its interpretation, by workers self-management and Company’s Dispute Adjudication Boards (CDAB). It was possible to notice the sign of appropriating privileges by determined employees groups not-arising from the existing law, but being a sign of aspirations to ensure a higher position for oneself in the unit through certain acquaintances and in consequence achieving common benefits, etc. informally. The article constitutes only a starting point for further in-depth studies covering employee issues in all tobacco industry in Poland.